2015
DOI: 10.4236/ojped.2015.52016
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Intake in Relation to Body Mass Index and Fatness in Thai School-Aged Children

Abstract: An emerging evidence suggests that dietary calcium may play a role in the regulation of body weight in humans. This study examined the relationship of calcium intake with body mass index and body fatness in Thai children. Methods: A cross-sectional study in 1570, 6 -12 year-old children were conducted in representative provinces of Thailand. Body weight, height, sitting height and 4 sites skinfolds thickness were measured as well as the dietary intake using a 24 h recall and a food frequency questionnaire (FFQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
2
0
1
Order By: Relevance
“…About 51.7% of respondents had calcium intake deficiency with normal nutritional status. The result of this research was in accordance to Yamborisut et al (2015) which found calcium intake was correlated to body weight (p=0.01) and Body Mass Index (p=0.025). Calcium is needed by teenagers for bone growth and reducing pain during menstruation.…”
Section: Discussionsupporting
confidence: 89%
“…About 51.7% of respondents had calcium intake deficiency with normal nutritional status. The result of this research was in accordance to Yamborisut et al (2015) which found calcium intake was correlated to body weight (p=0.01) and Body Mass Index (p=0.025). Calcium is needed by teenagers for bone growth and reducing pain during menstruation.…”
Section: Discussionsupporting
confidence: 89%
“…Kalsium mempengaruhi laju lipogenesis (sintesis lemak) dan lipolisis (pemecahan lemak) (Zemel et al, 2000). Penelitian pada anak sekolah di Thailand tahun 2015 menunjukkan bahwa asupan kalsium yang rendah berhubungan dengan indeks massa tubuh (IMT) dan lemak tubuh yang lebih tinggi pada anak (Yamborisut et al, 2015). Asupan vitamin D rendah merupakan prediktor obesitas bagi laki-laki dan perempuan di bawah usia 70 tahun (Kamycheva, et al, 2003).…”
Section: Pendahuluanunclassified
“…Calcium is a bone formation mineral that works complementary to the process of matrix formation, deposits in the formation of bone tissue so that if calcium deficiency occurs it will inhibit cell division, growth and tissue repair that will affect body weight and height 7 . Zinc is one of the micronutrients that play a very important role in the growth and development of toddlers, where zinc plays a role in the enzyme system, hormones, immunity and reproductive function.…”
Section: Introductionmentioning
confidence: 99%